INTEGRATIVE MODEL OF FOREIGN LANGUAGE TEACHING IN ACADEMIC AND PROFESSIONAL COMMUNICATION - Xudoyarova Dildora Najmidinovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines an integrative model of foreign language teaching designed to develop students’ competencies in academic and professional communication. The study analyzes how combining linguistic, cultural, and professional knowledge through interdisciplinary and integrative teaching methods enhances communicative skills, critical thinking, and adaptability. The model incorporates interactive techniques, project-based learning, and real-world tasks to provide authentic learning experiences. Findings indicate that the integrative approach improves students’ ability to communicate effectively in academic and professional contexts, fosters intercultural awareness, and strengthens both analytical and practical competencies.